2010
DOI: 10.3109/09687688.2010.495354
|View full text |Cite
|
Sign up to set email alerts
|

Sorting things out through endoplasmic reticulum quality control

Abstract: The endoplasmic reticulum (ER) is a highly organized and specialized organelle optimized for the production of proteins. It is comprised of a highly interconnected network of tubules that contain a large set of resident proteins dedicated to the maturation and processing of proteins that traverse the eukaryotic secretory pathway. As protein maturation is an imperfect process, frequently resulting in misfolding and/or the formation of aggregates, proteins are subjected to a series of evaluation processes within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 136 publications
(226 reference statements)
1
11
0
Order By: Relevance
“…Recently, it has been reported that EDEM1, OS-9 and XTP3-B (and their yeast orthologs; Hanna et al [2012]) may use their ML or MRH domains to associate with oligosaccharides displayed by the type I membrane protein SEL1L, a component of the dislocation machinery containing the E3 ubiquitin ligase HRD1 (Christianson et al, 2012;Christianson et al, 2008;Cormier et al, 2009;Satoh et al, 2010). This led to challenge the ''mannose timer model'' of protein quality control and to propose an alternative ''docking model'' of protein quality control in which oligosaccharides may serve as docking sites for EDEM1 and OS-9 at the SEL1L/HRD1 dislocon, rather than as signal tagging misfolded polypeptides for destruction (Aebi et al, 2010;Tamura et al, 2010). In this work, we have evaluated the consequences and the biological relevance of the oligosaccharide-based association between EDEM1 or OS-9 and SEL1L.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that EDEM1, OS-9 and XTP3-B (and their yeast orthologs; Hanna et al [2012]) may use their ML or MRH domains to associate with oligosaccharides displayed by the type I membrane protein SEL1L, a component of the dislocation machinery containing the E3 ubiquitin ligase HRD1 (Christianson et al, 2012;Christianson et al, 2008;Cormier et al, 2009;Satoh et al, 2010). This led to challenge the ''mannose timer model'' of protein quality control and to propose an alternative ''docking model'' of protein quality control in which oligosaccharides may serve as docking sites for EDEM1 and OS-9 at the SEL1L/HRD1 dislocon, rather than as signal tagging misfolded polypeptides for destruction (Aebi et al, 2010;Tamura et al, 2010). In this work, we have evaluated the consequences and the biological relevance of the oligosaccharide-based association between EDEM1 or OS-9 and SEL1L.…”
Section: Introductionmentioning
confidence: 99%
“…Retention in the subcellular compart ments is an indication of protein misfold ing, often leading to degradation (37). This observation prompted us to quan tify the cellular expression levels of the different pendrin protein variants, on the basis of the hypothesis that abundance of variants with significant retention in the ER should be reduced with respect to variants with targeting to the PM.…”
Section: Discussionmentioning
confidence: 99%
“…The quality control machinery of the secretory pathway recognizes misfolded proteins and targets them for degradation (17). To be sure that domain 2 was properly folded, we tested its oligomeric state by gel filtration chromatography.…”
Section: Figurementioning
confidence: 99%